Persepsi Etis Auditor pada Kantor Akuntan Publik dan Akuntan Pendidik pada Praktik Manajemen Laba - Sukma K, Putu Javani; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 24 No 3 (2018)DO - 10.24843/EJA.2018.v24.i03.p29, 2018)
The purpose of this research is to know the difference of auditor's ethical perception on public accounting firm and educator accountant on earnings management practice in terms of operational manipulation type, accounting manipulation, manipulation direction, materiality and manipulation tendency. Sample in this research is auditor at Public Accountant Office counted 41 people and accountant educator counted 30 people, with total sample 71 people. Sampling in this research using purposive sampling method with analysis technique which done in this research using Mann Whitney analysis technique. The result of the research shows that there is difference of ethical perception between auditor at Public Accountant Office and educator accountant on earnings management practice based on accounting manipulation type and manipulation direction. While there is no difference of ethical perception between auditor at Public Accountant Office and educator accountant on earnings management practice based on operational manipulation type, materiality and manipulation tendency. Keywords : Perception, Ethics, Profit Management, Auditor, Accountant